If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(6y + -7) + -1(2y + 2) = 0 Reorder the terms: 6(-7 + 6y) + -1(2y + 2) = 0 (-7 * 6 + 6y * 6) + -1(2y + 2) = 0 (-42 + 36y) + -1(2y + 2) = 0 Reorder the terms: -42 + 36y + -1(2 + 2y) = 0 -42 + 36y + (2 * -1 + 2y * -1) = 0 -42 + 36y + (-2 + -2y) = 0 Reorder the terms: -42 + -2 + 36y + -2y = 0 Combine like terms: -42 + -2 = -44 -44 + 36y + -2y = 0 Combine like terms: 36y + -2y = 34y -44 + 34y = 0 Solving -44 + 34y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '44' to each side of the equation. -44 + 44 + 34y = 0 + 44 Combine like terms: -44 + 44 = 0 0 + 34y = 0 + 44 34y = 0 + 44 Combine like terms: 0 + 44 = 44 34y = 44 Divide each side by '34'. y = 1.294117647 Simplifying y = 1.294117647
| y+18=32 | | y/11=1 | | 35x-12x= | | 13-z=8 | | (9t-5)(9t+5)= | | y/1=4 | | 13/y=1 | | z+15=30 | | showx+y=180 | | 4c=-3 | | 18y=180 | | 18+2n=4x-9 | | 16z=176 | | XY+2x+4y=202 | | -1/5x8 | | -59+23=-2x+11x | | 3z=51 | | 4(2-2n)+8=-6-(3n+8) | | 12u^3+20u^2-48u=0 | | 9x+10+3x-4=180 | | (4x-8)-(7x-9)= | | (64u^6v^12)^1/3 | | (7/24)/(1/6) | | 8(v+3)-2v=2(3v+4)-13 | | 2x^2-2x-6=x^2-x-4 | | f+8squared=3squared | | x-13x=3x-6 | | 36=12x+x^2 | | y=-x+6x-12 | | a(5)=6 | | 3+11x-1=9x+29-7x | | 4.9x-10x/3-12 |